A new synonym of Capnia oblata Chen & Du, 2017 (Plecoptera: Capniidae) based on morphological and molecular data - Yang, Xiao; Du, Yu-Zhou (Zootaxa, 2025)
We recently examined specimens of the genus Capnia Pictet 1841 from Sichuan Province, China, and a new synonym is established based on morphological and molecular data. Capnia xiei Chen & Du, 2017 is herein established as a junior synonym of Capnia oblata Chen & Du, 2017.